Effects of Olympic Combat Sports on Cardiorespiratory Fitness in Non-Athlete Population: A Systematic Review of Randomized Controlled Trials - Herrera-Valenzuela, T (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This systematic review aimed to assess the available body of published peer-reviewed articles related to the effects of Olympic combat sports (OCS) on cardiorespiratory fitness (CRF) in the non-athlete population. The methodological quality and certainty of evidence were evaluated using PRISMA, TESTEX, RoB, and GRADE scales. The protocol was registered in PROSPERO (code: CRD42023391433). From 4133 records, six randomized controlled trials were included, involving 855 non-athletes (mean age = 27.2 years old). The TESTEX scale reported all studies with a ≥ 60% (moderate-high quality) score. The GRADE scale indicated moderate to low certainty of evidence. It was only possible to perform a meta-analysis on direct methods to maximum oxygen consumption (VO2max). The main results indicated significant differences in favor of OCS compared to active/passive controls in VO2max (SMD = 4.61; 95%CI = 1.46 to 7.76; I2 = 99%; p = 0.004), while the individual results of the studies reported significant improvements in favor of the OCS on the indirect methods of the CRF. OCS improved CRF in a healthy non-athlete population of different ages, specifically showing a significant improvement in VO2max with direct tests, such as cardiopulmonary tests. However, moderate to low certainty of evidence is reported, so no definitive recommendations can be established. © 2023 by the authors.